2005
DOI: 10.1016/j.jog.2005.06.012
|View full text |Cite
|
Sign up to set email alerts
|

The GGOS as the backbone for global observing and local monitoring: A user driven perspective

Abstract: A key geodetic contribution to both the three Global Observing Systems and initiatives like the European Global Monitoring for Environment and Security is an accurate, long-term stable, and easily accessible reference frame as the backbone. Many emerging scientific as well as non-scientific high-accuracy applications require access to an unique, technique-independent reference frame decontaminated for short-term fluctuations due to global Earth system processes. Such a reference frame can only be maintained an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…However, geodetic GPS processing is now aiming for rates of movement known to well within 1 mm/year (Plag 2005). There is a wide range of applications, varying from vertical land motion estimates for calibration of tide gauges and comparison with glacial isostatic adjustment (Bouin and Wöppelmann 2010), to tectonic strain (e.g.…”
Section: Significance Of Higher-order Ionospheric Correctionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, geodetic GPS processing is now aiming for rates of movement known to well within 1 mm/year (Plag 2005). There is a wide range of applications, varying from vertical land motion estimates for calibration of tide gauges and comparison with glacial isostatic adjustment (Bouin and Wöppelmann 2010), to tectonic strain (e.g.…”
Section: Significance Of Higher-order Ionospheric Correctionsmentioning
confidence: 99%
“…There is a wide range of applications, varying from vertical land motion estimates for calibration of tide gauges and comparison with glacial isostatic adjustment (Bouin and Wöppelmann 2010), to tectonic strain (e.g. Calais et al 2005) and long term subsidence monitoring of oil rigs (Plag 2005). An excellent review of some of the many geodetic applications of GPS can be found in Herring (1999).…”
Section: Significance Of Higher-order Ionospheric Correctionsmentioning
confidence: 99%
“…User requirements for monitoring of such infrastructure are of the order of less than 1 cm for sub-daily to daily positions available with a latency of a few days, 2-3 mm on monthly to seasonal time scales, and 1 mm/yr for long-term stability (Plag, 2004).…”
Section: Positioning Changes In Positions and Displacementsmentioning
confidence: 99%